The Story of Baby Corn - Bhat, Jayant S.; Patil, B. S. (Indian Farming, 2015)
Corn will remain one of the important field crops in the developing countries. Considerable scope exists for promoting baby corn technology in the Asia-Pacific region. The baby corn industry provides opportunities for higher income, generates employment for the rural poor and potential for export. Besides, its use as vegetable provides additional source of nutrition to the consumers. Baby corn is expected to catch the attention of more and more consumers and farmers because of its superior taste and texture. Using local produce gives fresh and nutritious food and keeps small farmers in business.Thus, help supports the local economy and conserving natural resources (raw materials for transportation and packaging are saved). In order to harness these benefits, research and development support and appropriate policies at the national level are required. Hence, the Governments should therefore, concentrate on framing policies and development of human resources. In addition, government policies should encompass motivating young farmers and finding creative ways to sustain baby corn industry by involving personnel involved in both private and public sectors.